Risk of ventricular arrhythmia in cardiac resynchronization therapy responders and super-responders: a systematic review and meta-analysis. Issue 8 (26th January 2021) - Yuyun, Matthew F; Erqou, Sebhat A; Peralta, Adelqui O; Hoffmeister, Peter S; Yarmohammadi, Hirad; Echouffo Tcheugui, Justin B; Martin, David T; Joseph, Jacob; Singh, Jagmeet P
Abstract: Aims: Response to cardiac resynchronization therapy (CRT) is associated with improved survival, and reduction in heart failure hospitalization, and ventricular arrhythmia (VA) risk. However, the impact of CRT super-response [CRT-SR, increase in left ventricular ejection fraction (LVEF) to ≥ 50%] on VA remains unclear. Methods and results: We undertook a meta-analysis aimed at determining the impact of CRT response and CRT-SR on risk of VA and all-cause mortality. Systematic search of PubMed, EMBASE, and Cochrane databases, identifying all relevant English articles published until 31 December 2019. A total of 34 studies (7605 patients for VA and 5874 patients for all-cause mortality) were retained for the meta-analysis. The pooled cumulative incidence of appropriate implantable cardioverter-defibrillator therapy for VA was significantly lower at 13.0% (4.5% per annum) in CRT-responders, vs. 29.0% (annualized rate of 10.0%) in CRT non-responders, relative risk (RR) 0.47 [95% confidence interval (CI) 0.39–0.56, P  < 0.0001]; all-cause mortality 3.5% vs. 9.1% per annum, RR of 0.38 (95% CI 0.30–0.49, P  < 0.0001). The pooled incidence of VA was significantly lower in CRT-SR compared with CRT non-super-responders (non-responders + responders) at 0.9% vs. 3.8% per annum, respectively, RR 0.22 (95% CI 0.12–0.40, P  < 0.0001); as well as all-cause mortality at 2.0% vs. 4.3%, respectively, RR 0.47 (95% CI 0.33–0.66, P  < 0.0001). Conclusions: Cardiac resynchronization therapy super-responders have low absolute risk of VA and all-cause mortality. However, there remains a non-trivial residual absolute risk of these adverse outcomes in CRT responders. These findings suggest that among CRT responders, there may be a continued clinical benefit of defibrillators.